2022
DOI: 10.1002/arch.21919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glyphosate on the growth, development, and physiological functions of silkworm, Bombyx mori

Abstract: Glyphosate is an herbicide widely used worldwide, but whether it is safe to nontarget organisms is controversial. In this study, the lepidopteran model insect silkworm was used to investigate the effects of glyphosate residues. The LC 50 (72 h) of glyphosate on silkworm was determined to be 14875.98 mg/L, and after exposure to glyphosate at 2975.20 mg/L (a concentration comparable to that used for weed control in mulberry fields), silkworm growth was inhibited by 9.00%, total cocoon weight was lowered by 10.53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our previous study has shown that glyphosate exposure can inhibit silkworm growth and development, reduce total cocoon weight and digestive enzymes, and induce the histopathological changes in the midgut and oxidative stress (Feng et al, 2022). In this study, we used the silkworm, Bombyx mori , as the research subject, and performed RNA‐Seq to analyze the transcriptome profile of silkworm midgut after exposed to glyphosate at 2975.20 mg/L (a concentration commonly used at mulberry fields).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study has shown that glyphosate exposure can inhibit silkworm growth and development, reduce total cocoon weight and digestive enzymes, and induce the histopathological changes in the midgut and oxidative stress (Feng et al, 2022). In this study, we used the silkworm, Bombyx mori , as the research subject, and performed RNA‐Seq to analyze the transcriptome profile of silkworm midgut after exposed to glyphosate at 2975.20 mg/L (a concentration commonly used at mulberry fields).…”
Section: Discussionmentioning
confidence: 99%
“…Redox imbalance is considered as an important mechanism of glyphosate toxicity on nontarget organisms. Studies have shown that glyphosate exposure causes accumulation of H 2 O 2 and O 2− in silkworm midgut (Feng et al, 2022), and Cat can quickly decompose H 2 O 2 (Scandalios, 2005). This study found that the transcription level of Cat in silkworm midgut after glyphosate exposure was 1.93‐fold of the control group, which is consistent with our results; however, the transcript level of Jafrac1 , which encodes thiol peroxiredoxin, was downregulated (0.71‐fold of the control group).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations